Emotional Self-Awareness and Quarter Life Crisis in Final Year of Undergraduate Nursing Students - Rachmania, Diana; Zakiyyatul Fuadah, Dina (Journal of Applied Nursing and Health, 2023)
Background: A quarter-life crisis is when individuals experience an emotional crisis with negative feelings toward the future. Many responsibilities and demands on fourth-year students affect their psychology. A person with good self-awareness makes it easier to control emotions, read the surrounding situation, not be easily affected, and focus on himself. This study aims to analyse the relationship between self-awareness and quarter-life crisis in the final years of undergraduate nursing students. Methods: This research design is correlational with a cross-sectional approach. The sample in this study was 87 people, which was the whole population (Total Sampling). The research instrument used a self-awareness questionnaire and a quarter-life crisis questionnaire—data analysis using the Spearman Rank. Results: The study results showed that most respondents (55.2%) had sufficient emotional self-awareness, and most (52%) experienced a moderate quarter-life crisis. Analysis using the Spearman Rank test obtained a p-value of 0.018 with an error level of α = 0.05, meaning that there is a relationship between emotional self-awareness and quarter-life crisis with a strong category strength (r = -0.54) Conclusion: Some factors affect self-awareness, namely thoughts, feelings, knowledge behaviour, environment, and quarter-life crisis internal factors such as identity exploration, expectations, and religion, while external factors such as romantic relationships, work, family, and friends. Self-introspection strategies can increase self-awareness. Dealing with a crisis is not comparing yourself with others, communicating with parents, or finding professionals if the problem is getting complicated